Social Reactions to Sexual Assault Disclosure: The Role of Posttraumatic Cognitions - Morris, Jill M. (Journal of interpersonal violence, 2021)
Sexual assault can have a detrimental impact on women’s mental, physical, sexual, and interpersonal health and well-being. After experiencing sexual assault, 74% to 88% of individuals disclose the assault to someone they trust. After such disclosures, individuals experience both perceived positive and negative reactions. While positive reactions may be protective and aid in recovery, negative reactions can contribute to feelings of self-blame and maladaptive beliefs about the cause of the assault. Previous studies have shown independent associations between social reactions, negative cognitions, and posttraumatic stress symptoms (PTSS) following sexual assault. However, prior research has not explored the joint role of social reactions and posttraumatic cognitions in relationship to PTSS and sexual assertiveness. Moreover, the mechanism regarding these associations is not well established. The present study tested a path model of the effects of social reactions (positive and negative) to disclosure of sexual assault on posttraumatic cognitions, PTSS, and sexual assertiveness in college women. It was hypothesized that posttraumatic cognitions would mediate the relationship between social reactions and both sexual assertiveness and PTSS. A total of 102 college women participated in the study and completed measures of Sexual Experiences, Social Reactions, Posttraumatic Cognitions, PTSS, and Sexual Assertiveness. Results indicated that negative social reactions were indirectly associated with sexual assertiveness through posttraumatic cognitions. Social reactions were indirectly associated with PTSS partially through posttraumatic cognitions. Furthermore, there was a direct relationship between negative social reactions and PTSS. Positive social reactions were not significantly associated with outcome variables. Results highlight the influential nature of negative social reactions and posttraumatic cognitions. The importance of educating bystanders on the influence of social reactions is further discussed.